High-voltage electrolyte, lithium ion battery and electric device
Patent Information
- Application Number
- CN202311519562.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-14
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-11-14
AI Technical Summary
[0019]本发明的锂离子电池获得压实密度为4.20-4.25g/cm3的正极活性物质层,可通过调整正极极片制造过程中冷压工序的压力为60-65T,可使正极极片辊压后的压实密度处于此范围内。本发明的电解液体系与压实密度为4.20-4.25g/cm3的钴酸锂正极搭配,可在保证高能量密度的同时抑制LCO在高电压循环过程中产生裂纹,抑制钴溶出,改善充电性能。若压实密度过大,会导致无法较好地抑制钴溶出,对电池的性能造成负面影响;若压实密度过低,会导致第一化合物过量,造成电池体系整体的阻抗偏高,影响电池的性能。
Smart Images

Figure QLYQS_1 
Figure QLYQS_2 
Figure BDA0004550064510000021
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium batteries, and more particularly to a high-voltage electrolyte, a lithium-ion battery, and an electrical device. Background Technology
[0002] With the advancement of science and technology and the continuous improvement of electronic device performance, people have increasingly higher requirements for battery performance. One of the most important indicators of battery performance is range, which is mainly determined by the positive and negative electrode materials. In certain niche areas, such as drones and Bluetooth headsets, there are even higher requirements for battery cycle performance and charge / discharge rate. While meeting cycle life requirements, it is also necessary to consider high-rate charge / discharge performance, and to install larger capacity lithium-ion batteries within a limited space. Therefore, it is necessary to improve the volumetric energy density of lithium-ion batteries. Currently, there are two effective paths to improve the energy density of lithium-ion batteries: one is to increase the battery voltage, and the other is to increase the specific capacity of the positive and negative electrode active materials. Increasing the battery voltage leads to more severe side reactions of the electrolyte at the positive electrode interface, placing higher demands on the electrolyte performance.
[0003] In view of this, it is indeed necessary to provide a technical solution to the above problems. Summary of the Invention
[0004] The purpose of this invention is to address the shortcomings of existing technologies by providing a high-voltage electrolyte for lithium-ion batteries. This electrolyte is adaptable to high-voltage lithium cobalt oxide systems above 4.53V, significantly improves the stability of the interface between the positive and negative electrode materials and the electrolyte, suppresses cracks on the surface of the positive and negative electrode material particles during cycling, enhances the stability of the positive electrode material surface, inhibits the dissolution of transition metal ions, and improves the room temperature / high temperature cycling performance, high temperature storage performance, and thermal performance of lithium-ion batteries.
[0005] To achieve the above objectives, the present invention adopts the following technical solution:
[0006] A high-voltage electrolyte for a lithium-ion battery includes a lithium salt, an organic solvent, and a film-forming additive, wherein the film-forming additive includes a first film-forming additive and a second film-forming additive; the first film-forming additive includes a first compound of formula I and a second compound of formula II.
[0007]
[0008] R1-R5 are each independently selected from alkyl groups with 1-10 carbon atoms, whether substituted or unsubstituted; when substituted, the substituents are selected from O or F atoms.
[0009] The first compound of Formula I accounts for 0.05-6 wt% of the total amount of the high-voltage electrolyte, and the second compound of Formula II accounts for 0.05-5 wt% of the total amount of the high-voltage electrolyte.
[0010] Preferably, the first compound comprises a compound with the following structural formula:
[0011]
[0012] Preferably, the first compound accounts for 0.1-3 wt% of the total amount of the high-voltage electrolyte; the second compound accounts for 0.1-3 wt% of the total amount of the high-voltage electrolyte.
[0013] Preferably, the lithium salt comprises at least one of lithium hexafluorophosphate (LiPF6), lithium difluorophosphate (LiDFP), lithium difluorobis(oxalate) phosphate (LiODFP), lithium tetrafluorooxalate phosphate (LiOTFP), lithium bis(oxalate) borate (LiBOB), lithium difluorobis(oxalate) borate (LiODFB), lithium tetrafluoroborate (LiBF4), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), and lithium bis(fluorosulfonyl)imide (LiFSI).
[0014] Preferably, the lithium salt accounts for 10-20 wt% of the total amount of the high-voltage electrolyte.
[0015] Preferably, the second film-forming additive includes at least one of 1,3-propanesulfonate lactone (PS), vinyl sulfate (DTD), fluoroethylene carbonate (FEC), tris(trimethylsilane)borate (TMSB), and tris(trimethylsilane)phosphate (TMSP).
[0016] Preferably, the second film-forming additive accounts for 0.1-20 wt% of the total amount of the high-voltage electrolyte.
[0017] A second objective of this invention is to provide a lithium-ion battery, comprising a positive electrode, a negative electrode, a separator spaced between the positive electrode and the negative electrode, and the aforementioned high-voltage electrolyte.
[0018] In some embodiments, the positive electrode active material of the positive electrode sheet is lithium cobalt oxide, and the compaction density of the positive electrode active material layer of the positive electrode sheet is 4.20-4.25 g / cm³. 3 .
[0019] The lithium-ion battery of this invention achieves a compaction density of 4.20-4.25 g / cm³. 3The positive electrode active material layer can be adjusted so that the compaction density of the positive electrode sheet after rolling is within this range by adjusting the pressure of the cold pressing process during the manufacturing of the positive electrode sheet to 60-65T. The electrolyte system of this invention has a compaction density of 4.20-4.25 g / cm³. 3 The combination of lithium cobalt oxide cathode and lithium cobalt oxide can suppress LCO cracking during high-voltage cycling, inhibit cobalt dissolution, and improve charging performance while ensuring high energy density. If the compaction density is too high, it will lead to insufficient suppression of cobalt dissolution, which will negatively affect the battery performance; if the compaction density is too low, it will lead to an excess of the first compound, resulting in a higher overall impedance of the battery system and affecting the battery performance.
[0020] A third objective of the present invention is to provide an electrical device comprising the aforementioned lithium-ion battery.
[0021] Compared to existing technologies, the advantages of this invention are as follows: The high-voltage electrolyte provided by this invention contains a first film-forming additive comprising a first compound of Formula I and a second compound of Formula II. The four cyano groups (-CN) in the first compound of Formula I possess strong electronegativity, allowing them to tightly adsorb onto the surface of the positive electrode active material. This effectively complexes the Co element dissolved from the surface of the LiCoO2 particles, inhibiting side effects such as electrolyte decomposition, DCR (Direct Current Resistance) increase, and SEI (Solid Electrolyte Interface) malignant growth, thereby improving the performance of high-voltage lithium cobalt oxide batteries above 4.53V. The oxygen atoms in the first compound of Formula I possess two lone pairs of electrons, which play a role in transporting Li during charging and discharging. + Its function is to help Li + The compound exhibits good migration properties and high stability, effectively improving the thermal stability of lithium-ion batteries. The second compound of Formula II can remove moisture and HF from the electrolyte, reducing lithium salt decomposition and HF corrosion of the positive electrode active material. Simultaneously, the second compound of Formula II can form a thin and tough SEI film on the negative electrode surface, effectively protecting the negative electrode active material and extending the cycle life of the lithium-ion battery. Furthermore, the second compound of Formula II contains a Hückel anion structure, exhibiting good stability and contributing to improved high-temperature performance of lithium-ion batteries. Through the synergistic effect of the first compound containing Formula I and the second compound containing Formula II, side reactions of LiCoO2 at high potentials can be effectively reduced, increasing the Young's modulus of the SEI on both positive and negative electrode surfaces, effectively reducing the probability of SEI rupture during cycling, and improving the battery's cycle performance. Detailed Implementation
[0022] To make the technical solution and advantages of the present invention clearer, the present invention and its beneficial effects will be described in further detail below in conjunction with specific embodiments, but the embodiments of the present invention are not limited thereto.
[0023] Example 1
[0024] A lithium-ion battery includes a positive electrode, a negative electrode, a separator spaced between the positive electrode and the negative electrode, and a high-voltage electrolyte.
[0025] (1) Preparation of high-voltage electrolyte: In an argon-filled glove box, ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), and propyl propionate (PP) were mixed in a mass ratio of EC:PC:DEC:PP = 2:2:3:3 to obtain a solvent. Then, lithium hexafluorophosphate (LiPF6) at 14 wt% of the total electrolyte weight was slowly added to the solvent. Finally, compound A (CAS No: 2465-94-3), compound B (CAS No: 761441-54-7), 1 wt% of 1,3-propanesulfonate lactone (PS), and 1 wt% of tris(trimethylsilane)borate (TMSB) were added at 1 wt% of the total electrolyte weight. After stirring evenly, the high-voltage electrolyte of Example 1 was obtained; the solvent content was 79 wt% of the total electrolyte weight.
[0026] (2) Preparation of the positive electrode sheet: The active material of the positive electrode sheet is lithium cobalt oxide (LiCoO2), the conductive agent is conductive carbon black Super P, and the binder is polyvinylidene fluoride (PVDF). The active material LiCoO2, conductive carbon black Super P, and PVDF are mixed in a weight ratio of 97:1.7:1.3, and then added to N-methylpyrrolidone (NMP). The mixture is thoroughly mixed to prepare the lithium-ion battery positive electrode slurry. The lithium-ion battery positive electrode slurry is coated onto a current collector aluminum foil, vacuum dried at 85℃ for 4 hours, and then cold-pressed (cold pressing pressure 60T, rolling speed 10m / min). The foil is then trimmed, cut, and slit. After drying under vacuum at 85℃ for 4 hours, electrode tabs are welded, resulting in a compacted density of 4.2 g / cm³ for the positive electrode active material layer. 3 The positive electrode sheet.
[0027] (3) Preparation of negative electrode sheet: The active material of the negative electrode sheet is graphite, the conductive agent is carbon nanotubes (CNT), the thickener is sodium carboxymethyl cellulose (CMC), and the binder is styrene-butadiene rubber (SBR). The active material graphite, the conductive agent carbon nanotubes (CNT), the thickener sodium carboxymethyl cellulose (CMC), and the binder styrene-butadiene rubber (SBR) are mixed in a weight ratio of 95:1.3:1.2:2.5, and deionized water is added and mixed evenly to prepare a negative electrode slurry. The negative electrode slurry is coated on the current collector copper foil, vacuum dried at 85℃ for 4h, and then cold pressed at a pressure of 30T and a rolling speed of 15m / min. Then, the edges are cut, the sheets are cut, and the sheets are slit. The negative electrode sheet of lithium-ion battery is obtained by drying at 85℃ under vacuum for 12h.
[0028] (4) Preparation of lithium-ion battery: The prepared positive electrode, separator and negative electrode are stacked in sequence, with the separator in the middle of the positive electrode and negative electrode, and wound to obtain bare cell; the bare cell is placed in aluminum-plastic film outer packaging, the electrolyte prepared above is injected into the dried cell, and then it is packaged, left to stand, formed, shaped and capacity tested to complete the preparation of lithium-ion soft pack battery.
[0029] Examples 1 to 26, Comparative Examples 1 to 9
[0030] Repeat the steps of Example 1 according to the specified component contents of the electrolytes in Examples 2 to 26 and Comparative Examples 1 to 9 in Table 1.
[0031] Comparative Example 8: The only difference between it and Example 1 is that the compaction density of the positive electrode active material layer is 4.1 g / cm³. 3 The cold pressing conditions were 30T; other conditions were the same as in Example 1.
[0032] Comparative Example 9: The only difference between it and Example 1 is that the compaction density of the positive electrode active material layer is 4.3 g / cm³. 3 The cold pressing conditions were 90T pressure, and other conditions were the same as in Example 1.
[0033] The lithium-ion batteries prepared according to the corresponding examples and comparative examples were subjected to relevant performance tests, and the test results are shown in Table 2.
[0034] Table 1: Component content (by weight percentage of electrolyte) of Examples 1 to 26 and Comparative Examples 1 to 9
[0035]
[0036]
[0037]
[0038]
[0039] Lithium-ion battery performance testing
[0040] The lithium-ion batteries prepared in Examples 1 to 26 and Comparative Examples 1 to 9 were subjected to the following relevant performance tests:
[0041] (1) Room temperature cycle performance test: In an environment of 25℃, the battery after capacity division is charged to 4.55V at a constant current and constant voltage of 1.2C, with a cutoff current of 0.05C, and then discharged to 3.0V at a constant current of 0.5C. This cycle is repeated. After 400 charge-discharge cycles, the capacity retention rate on the 400th cycle is calculated using the following formula:
[0042] 400-week cycle capacity retention (%) = (400-week cycle discharge capacity / initial cycle discharge capacity) × 100%.
[0043] (2) High-temperature cycle performance test: In an environment of 45℃, the battery after capacity division is charged to 4.55V at a constant current and constant voltage of 1.5C, with a cutoff current of 0.05C, and then discharged to 3.0V at a constant current of 0.5C. This cycle is repeated for 300 charge-discharge cycles. The capacity retention rate at the 300th cycle is calculated using the following formula:
[0044] 300-week cycle capacity retention (%) = (300-week cycle discharge capacity / initial cycle discharge capacity) × 100%.
[0045] (3) Thermal shock performance: Under 25℃ environmental conditions, discharge to 3.0V with a given current of 0.2C; rest for 5min; charge to 4.55V with a charging current of 0.2C. When the cell voltage reaches 4.55V, switch to 4.55V constant voltage charging until the charging current ≤ cut-off current 0.05C; after resting for 1h, put the cell into an oven. The oven temperature rises to 132±2℃ at a rate of 5±2℃ / min and is maintained for 60min before stopping. The judgment criterion is that the cell does not catch fire or explode.
[0046] (4) 85℃ 24h High-Temperature Storage Test: The battery was charged and discharged once at 0.5C at room temperature (4.55V-3.0V), and the discharge capacity C0 before storage was recorded. Then, the battery was charged to 4.55V at constant current and constant voltage (100% SOC). The thickness d1 of the battery before high-temperature storage was measured using a PPG battery thickness gauge (600g). The battery was then stored in an 85℃ constant temperature chamber for 24 hours. After storage, the battery was removed and the thermal thickness d2 after storage was measured. The battery thickness expansion rate after 24 hours of storage at 85℃ was calculated. After the battery cooled at room temperature for 24 hours, it was discharged again at 0.5C at constant current to 3.0V, and then charged to 4.55V at 0.5C at constant current and constant voltage. The discharge capacity C1 and charging capacity C2 after storage were recorded. The remaining capacity and recovery rate of the battery after 24 hours of storage at 85℃ were calculated using the following formula:
[0047] Thickness expansion rate after storage at 85℃ for 24 hours = (d2-d1) / d1*100%;
[0048] The remaining capacity after storage at 85℃ for 24 hours is calculated as C1 / C0 * 100%.
[0049] Capacity recovery rate after storage at 85℃ for 24 hours = C2 / C0*100%.
[0050] The results of the above performance tests are shown in Table 2.
[0051] Table 2. Performance test results of lithium-ion batteries in each embodiment and comparative example.
[0052]
[0053]
[0054]
[0055] The performance test results for the 132℃ thermal shock in Table 2 are as follows: 6 / 6 means that 6 samples out of 6 cells passed the test; 3 / 6 means that 3 samples out of 6 cells passed the test, and so on.
[0056] A comparison of the test results of Examples 1-26 and Comparative Examples 1-9 in Table 2 shows that the introduction of the first compound A of Formula I into the high-voltage electrolyte of the present invention can effectively improve the cycle performance and high-temperature performance of lithium-ion batteries. The four cyano groups contained in the structure of the first compound A of Formula I have strong electronegativity and can be tightly adsorbed onto the surface of the positive electrode active material. This effectively complexes the Co element on the surface of the LiCoO2 particles of the positive electrode active material, inhibiting the dissolution of cobalt ions and the resulting electrolyte decomposition, DCR growth, and SEI malignant growth, thereby improving the cycle performance of lithium-ion batteries.
[0057] A comparison of the test results of Examples 1-26 and Comparative Examples 1-9 in Table 2 shows that the introduction of the second compound B of Formula II into the high-voltage electrolyte of the present invention can effectively improve the cycle performance and high-temperature performance of the battery. The second compound B of Formula II can remove water and HF from the electrolyte, reducing the decomposition of lithium salts and the corrosion of the positive electrode active material by HF. Simultaneously, the second compound B of Formula II can form a thin and robust SEI film on the negative electrode surface, effectively protecting the negative electrode active material and extending the cycle life of the battery. Furthermore, its structure contains a Hückel anionic structure, which exhibits good stability and contributes to improved high-temperature performance.
[0058] As can be seen from Example 1 and Comparative Examples 8 and 9, the compaction density of the positive electrode film is <4.2 g / cm³. 3At this point, the battery performance is not significantly improved. This is because a low compaction density of the positive electrode active material layer leads to an excess of the first compound, resulting in higher overall battery impedance and performance degradation. However, a compaction density > 4.25 g / cm³... 3 When the positive electrode active material particle skeleton is damaged and the surface coating layer is severely broken, a large number of cracks will appear on the particle surface. In the early stage of cycling, severe dissolution of transition metal ions will occur, causing serious deterioration of cycling performance, high-temperature storage performance and safety performance. At this time, the combination of Formula I and Formula II cannot play an effective role.
[0059] The high-voltage electrolyte of the present invention, through the synergistic effect of the first compound A of Formula I and the second compound B of Formula II, can effectively reduce the side reactions of LiCoO2 at high potentials and increase the Young's modulus of the SEI on the positive and negative electrode surfaces, effectively reducing the probability of SEI rupture during cycling, improving the cycle performance of lithium-ion batteries, and is suitable for high-voltage lithium cobalt oxide (LiCoO2) systems of 4.53V and above.
[0060] In the embodiments provided by the present invention, the negative electrode active material can also be silicon-carbon active material SiC or silicon-oxygen active material SiO. x The adhesive may also be polyacrylic acid (PAA).
[0061] Based on the disclosure and teachings of the foregoing specification, those skilled in the art can make changes and modifications to the above embodiments. Therefore, the present invention is not limited to the specific embodiments described above, and any obvious improvements, substitutions, or modifications made by those skilled in the art based on the present invention are within the scope of protection of the present invention. Furthermore, although some specific terms are used in this specification, these terms are only for convenience of explanation and do not constitute any limitation on the present invention.
Claims
1. A lithium-ion battery, characterized in that, The electrolyte includes a positive electrode, a negative electrode, a separator between the positive electrode and the negative electrode, and a high-voltage electrolyte. The high-voltage electrolyte includes a lithium salt, an organic solvent, and a film-forming additive. The film-forming additive includes a first film-forming additive and a second film-forming additive. The first film-forming additive includes a first compound of formula I and a second compound of formula II. R1-R5 are each independently selected from alkyl groups with 1-10 carbon atoms, whether substituted or unsubstituted; when substituted, the substituents are selected from O or F atoms. The first compound of Formula I accounts for 0.05-6 wt% of the total amount of the high-voltage electrolyte, and the second compound of Formula II accounts for 0.05-5 wt% of the total amount of the high-voltage electrolyte. The positive electrode active material of the positive electrode sheet is lithium cobalt oxide, and the compaction density of the positive electrode active material layer of the positive electrode sheet is 4.20-4.25 g / cm³. 3 .
2. The lithium-ion battery according to claim 1, characterized in that, The first compound includes compounds with the following structural formulas: 。 3. The lithium-ion battery according to claim 1 or 2, wherein the first compound accounts for 0.1-3 wt% of the total amount of the high-voltage electrolyte; and the second compound accounts for 0.1-3 wt% of the total amount of the high-voltage electrolyte.
4. The lithium-ion battery according to claim 1, characterized in that, The lithium salt includes at least one of lithium hexafluorophosphate (LiPF6), lithium difluorophosphate (LiDFP), lithium difluorobis(oxalate) phosphate (LiODFP), lithium tetrafluoro(oxalate) phosphate (LiOTFP), lithium bis(oxalate) borate (LiBOB), lithium difluoro(oxalate) borate (LiODFB), lithium tetrafluoroborate (LiBF4), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), and lithium bis(fluorosulfonyl)imide (LiFSI).
5. The lithium-ion battery according to claim 1 or 4, characterized in that, The lithium salt accounts for 10-20 wt% of the total volume of the high-voltage electrolyte.
6. The lithium-ion battery according to claim 1, characterized in that, The second film-forming additive includes at least one of 1,3-propanesulfonate lactone (PS), vinyl sulfate (DTD), fluoroethylene carbonate (FEC), tris(trimethylsilane)borate (TMSB), and tris(trimethylsilane)phosphate (TMSP).
7. The lithium-ion battery according to claim 1 or 6, characterized in that, The second film-forming additive accounts for 0.1-20 wt% of the total amount of the high-voltage electrolyte.
8. An electrical device, characterized in that, Including the lithium-ion battery as described in any one of claims 1 to 7.
Citation Information
Patent Citations
High-temperature stable electrolyte and lithium ion battery thereof
CN110061291A
Tetracyano-containing nitrile ether electrolyte additive, electrolyte and lithium ion battery
CN112768772A